On the Delay Interval in Which the Control Delay Systems are Stabilizable - Jiang Wei (Complexity)
In this paper, we firstly derive some criteria for considered control delay systems to be stabilizable and then get the interval of the control delay, in which the stabilizability of the systems can be kept.